Berkelanjutan, kesejakterahan, p Optimizing Sustainable Agricultural Practices in Improving the Welfare of Coffee Farmers: Case Study in Banyuwangi Regency: Optimalisasi Praktik Pertanian Berkelanjutan dalam Meningkatkan Kesejahteraan Petani Kopi: Studi Kasus di Kabupaten Banyuwangi - Sugiharto, Firsta Bagus; Rizal Dhofir; Abdul Hamid; Tomas Surandoko (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Sustainable agriculture is an important approach to improving the welfare of farmers in Indonesia, requiring understanding and application of sustainable technologies by many farmers. The community service program titled "Optimizing Sustainable Agricultural Practices to Improve the Welfare of Coffee Farmers: A Case Study in Banyuwangi Regency," was held on January 13-14, 2024, involving 20 participants. The choice of this topic was based on the urgent need to enhance agricultural sustainability in the face of climate change and technological challenges. This activity used methods such as mapping and initial analysis of coffee farming conditions, including identifying existing practices and challenges. Primary data was collected through interviews with farmers and local government, as well as secondary data such as agricultural statistics. This data was then qualitatively analyzed to identify common patterns, challenges, and opportunities. Subsequently, workshops and training sessions for farmers on various topics related to sustainable agricultural practices and farm management were conducted. Following this, the recommended sustainable agricultural practices were implemented and monitored to measure their impact on farmers' welfare. The results showed an increase in participants' knowledge and skills, farmer empowerment, and the formation of collaborative networks. Recommendations for further research include studies on economic impacts and socio-cultural aspects. Overall, this activity made a positive contribution to local agriculture, improved farmers' welfare, supported sustainable agriculture, and has the potential to become a model for implementing sustainable practices at the community level. Keywords: Coffee Farmers, Sustainability, Prosperity